Gestión de los residuos sólidos médico-forenses en el Instituto Nacional de Medicina Legal y Ciencias Forenses, Medellín, 2001 (2002)
ABSTRACT: In the National Institute of Legal Medicine and Forensic Sciences, North – West department, Medellin Headquarters, a research was made about the management of medical forensic solid residues, generated in the legal medical and forensic science process, which are done in these places. The results in this research allowed to determine deficiencies in the staff knowledge related to the principles for the right handling of medical forensic solid residues generates by the Institute and the health risks that they can cause. Furthermore, the data collected form weighting the medical forensic residues, determined a daily average production of 4040gr. of solid residues, form which 66% were dangerous.